Studies of Nucleation Phase of Mn-doped Cadmium-Selenide (CdSe) Quantum Dots Via Photoluminescence Spectroscopy - Hamizi, Nor Aliya; Sadidarto, Ahmad Bayhaki; Johan, Mohd Rafie (Malaysian NANO-An International Journal, 2021)
In this paper, we predict the nucleation phase of as-synthesized manganese (Mn) doped cadmium selenide (CdSe) quantum dots (QDs) at an intrinsic physical size of 3 (± 0.1 – 0.9) nm via photoluminescence (PL) studies. The nucleation phase was analyzed at temporal evolution (16, 46 and 90 mins) and temperature (210, 215 and 220 ºC) below the CdSe QDs reaction temperature (210 and 215 ºC) to it reaction temperature (220 ºC). The PL spectra`s observed to be against the QDs ripening behaviour of QDs since there are no prominent red-shift of PL spectra`s. However, the intensity of PL spectra`s shows to be varied with different temperatures and times.